A dual‐polarized cross‐dipole antenna with wide beam and high isolation for base station. Issue 10 (28th July 2020) - Hao, Jia‐Wen; Wei, Feng; Zhao, Xi‐Bei; Shi, Xiao Wei
Abstract: In this paper, a dual‐polarized cross‐dipole antenna with wide beam and high isolation is designed and analyzed for base station. The proposed antenna consists of two planar cross dipoles with four square patches, two L‐shaped microstrip lines, two ground plates, four parasitic patches, and a reflector. The square patches are placed between the center of cross dipoles to couple with L‐shaped microstrip lines. By introducing the parasitic patches, the wide beam can be realized. The measured results show that the proposed antenna achieves an impedance bandwidth (| S 11 | < −10 dB) of about 18.7% (1.9‐2.35 GHz) and an isolation better than 30 dB. A measured gain of 5.7 dBi and a half‐power beamwidth over 120° at the center frequency are obtained. Furthermore, the size of the proposed antenna is only 0.5 λ 0 × 0.5 λ 0 × 0.22 λ 0 ( λ 0 is wavelength at the center frequency).